An Orientation Sensor for Mobile Robots Using Differentials. (18th February 2013) - Lee, Wei-Chen; Cai, Cong-Wei
Without access to external guidance, such as landmarks or beacons, indoor mobile robots usually orientate themselves by using magnetic compasses or gyroscopes. However, compasses face interference from steel furniture, and gyroscopes suffer from zero drift errors. This paper proposes an orientation sensor that can be used on differentially driven mobile robots to resolve these issues. The sensor innovatively combines the general differentials and an optical encoder so that it can provide only the orientation information. Such a sensor has not been described in any known literature and is cost-efficient compared to the common method of using two encoders for differentially driven mobile robots. The kinematic analysis and the mechanical design of this sensor are presented in this paper. The maximum mean error of the proposed orientation sensor was about 0.7° during the component tests. The application of the sensor on a vacuum cleaning robot was also demonstrated. The use of the proposed sensor may provide less uncertain orientation data for an indoor differentially driven mobile robot.